The Development of Confident Attitude and Linguistic Intelligence of Students Through Usbu' Arabi in University - Mahmudah, Ummi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This study aims to explain the activities of Arabic Language Study Program students at INSURI Ponorogo as a means of developing self-confidence and stimulating linguistic intelligence. The method used is a case study. The research location is the INSURI Ponorogo campus, with a research focus on Usbu' 'Araby activities. Observation, interviews, and documentation carried out data collection techniques. Meanwhile, data analysis was carried out by data reduction, presentation, and conclusion. The study results stated that the Usbu' 'Arabi was a means of developing students' self-confidence and linguistic intelligence. Activities include; Muḥaḋarah (speech), Taqdm al-Qiṣaṣ (storytelling), Taqdīr Al-Syi'ru (appreciation of poetry), Taqdīr al-Naṡr (appreciation of poetry), Masraḥiyyah (drama) and Al-Khaṭ al-'Araby (calligraphy).